JKA 314 – Agama dan Masyarakat - JKA 321 – Agama dan Hubungan Sosial - Mei - Jun 2017 - PPPJJ, Pusat Pengajian Pendidikan Jarak Jauh (2017)
JKA 314 – Agama dan Masyarakat - JKA 321 – Agama dan Hubungan Sosial - Mei - Jun 2017